Implementation of The Role Playing Method to Improve Student Learning Outcomes in The Solar System Subject Science - Muzdalifah Muzdalifah; Ismail Ismail (CV. Dharma Samakta Edukhatulistiwa, 2023)
The research began with observations in May 2023, the purpose of this study was to describe how the role playing method improves student learning outcomes on the solar system at MI Mu'awanah Muslimin Muslimat. This study uses a class action research method in four stages. Each stage has four activities, namely as follows: preparing, implementing, observing, and contemplating. With observation sheet instruments, documentation, and a ten-question essay test, the research data consisted of an analysis of quantitative descriptions of the application of the role of playing learning methods. MI Mu'awanah Muslimin Muslimat class VI students are the subject of this study. After the data was collected, qualitative and quantitative data analysis was carried out. The results showed that MI Mu'awanah Muslimin Muslimat students in Samirejo village had utilized the planning, action, observation, and reflection stages of the role-playing learning approach starting from Cycles 1 and 2. The application of the role-playing method to solar science subjects at MI Mu 'awanah Muslimin Muslimat has the potential to improve student learning outcomes, with the percentage of learning outcomes as evidenced by the class average starting at 69% in the first cycle, and increasing to 88% in the second cycle. The role playing learning method can also be used with different materials, as evidenced by the findings of published researchers and the results are quite satisfactory. Implementation in the field of Limnology education.